2007
DOI: 10.1093/icb/icm079
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy, physics, and physiology of gas exchange surfaces: is there a universal function for pulmonary surfactant in animal respiratory structures?

Abstract: (Orgeig and Daniels) This surfactant symposium reflects the integrative and multidisciplinary aims of the 1st ICRB, by encompassing in vitro and in vivo research, studies of vertebrates and invertebrates, and research across multiple disciplines. We explore the physical and structural challenges that face gas exchange surfaces in vertebrates and insects, by focusing on the role of the surfactant system. Pulmonary surfactant is a complex mixture of lipids and proteins that lines the air-liquid interface of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 85 publications
0
23
0
1
Order By: Relevance
“…Efficient gas exchange requires a large enough surface to be continuously exposed to air while minimising the barriers for oxygen and carbon dioxide to diffuse between air and the blood compartment [1]. At the same time, a selection of combined defence mechanisms is required to help keep such an essentially exposed area sterile of potential pathogenic microorganisms.…”
Section: Pulmonary Surfactant Function and Dysfunctionmentioning
confidence: 99%
“…Efficient gas exchange requires a large enough surface to be continuously exposed to air while minimising the barriers for oxygen and carbon dioxide to diffuse between air and the blood compartment [1]. At the same time, a selection of combined defence mechanisms is required to help keep such an essentially exposed area sterile of potential pathogenic microorganisms.…”
Section: Pulmonary Surfactant Function and Dysfunctionmentioning
confidence: 99%
“…Their shape is rather cuboidal and they play a secretory role within the alveolar region. Indeed, pulmonary surfactant, a complex mixture of lipids and proteins that lines the alveolar surface, is synthesized, stored and secreted by type II pneumocytes (32,33). The main function of this surfactant layer is to avoid alveolar collapse by reducing surface tension within the alveoli, while the hydrophilic surfactant-associated proteins (SPs) A and D also play a role in the innate immune defense of the lungs (34,35).…”
Section: Histological Organization Of the Lungsmentioning
confidence: 99%
“…As a result, the interaction of temperature with the physicochemical properties of the lipid mixture has evolutionarily constrained the surfactant system, and has driven the evolution of surfactant lipid composition. Temperature has selected both the broad-scale evolutionary differences in surfactant lipid composition between the vertebrate groups, and the acute changes in surfactant composition, structure and function within individuals (Lang et al, 2005; Orgeig et al, 2007). For example, those vertebrate groups with lower preferred body temperatures, i.e.…”
Section: The Surfactant System and Evolution Of The Blood-gas Barrmentioning
confidence: 99%
“…Moreover, these compositional and functional changes are reversible upon arousal (Codd et al 2003; Lopatko et al 1999). It has been recently shown that these functional changes correlate with structural differences at the molecular level of the surfactant film (Orgeig et al 2007). The molecular, biophysical and thermodynamic mechanisms underlying these differences are currently being investigated.…”
Section: The Surfactant System and Evolution Of The Blood-gas Barrmentioning
confidence: 99%